Pemaknaan terhadap âKucingâ pada Kalangan Laki-Laki yang suka Seks dengan Laki-Laki (LSL) di Kota Semarang - Nafikadini, Iken (IKESMA, 2013)
Number of kucing currently is estimated to increase, but their existence is very closed. Kucing considered as an exclusive community because they not a lot of work on the streets as well as transgender sex workers. Most of the kucing has a brothel keeper who will set sex transactions. If donât have brothel keeper, they usually advertise themselves on free advertising website. On these ads, they will usually describe himselves physically and also publish his contact number. Furthermore, they also advertise himselves in the news media on the treatment and fitness segment, exclusively for men. The aims of this research is knowing the meaning of kucing on Men who have Sex with Men (MSM) in Semarang City. The method of this research using qualitative exploration with fenomenology approach. Â Informans of seven (7) âkucingâ through the Men who have Sex with Men (MSM) community which categorized in 3 groups, those are street, stay, and mobile. Data collected by indepth interview and analized which thematic content analysis. The result of this research shown that the meaning of âkucingâ appear from the interaction between the MSM groups. Such interactions lead to sign an agreement that the man who sold himself to the MSM group is termed a kucing. Symbol of kucing is negative because of its associations with the 2 things that are still stigmatized by society, namely prostitution and homosexuality, so they tend to restain and establish a different role when they are in the middle of the scope of the family and the community to cover the status as kucing. So most people do not know their identity as kucing.